2020
DOI: 10.38124/ijisrt20jun314
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle System for Optimum Road Safety with Anti-theft Capability

Abstract: Due to road traffic accidents, 6941 Filipinos died in 2010, and thousands more were wounded or disabled. Head and neck injuries are the main cause of death, severe injury, and motorcycle users ' disabilities. Motorcycle users make up a large proportion of those on the road who were killed. The study’s main purpose is to develop an MCU Based Motorcycle System for Optimum Road Safety with Anti-theft Capability that will help motorcycle riders to be safe while travelling in national roads. The researchers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…LITERATURE REVIEW Mao et al, (2018) used clustering analysis to identify crime focus areas while spatial autocorrelation technique works to detect areas with high and low clustering. Besides that, other study found the offender pick motorcycle off the ground and load it into a van (Godoy, 2020). This tactic shows that the offender can steal motorcycle when opportunity presents itself.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…LITERATURE REVIEW Mao et al, (2018) used clustering analysis to identify crime focus areas while spatial autocorrelation technique works to detect areas with high and low clustering. Besides that, other study found the offender pick motorcycle off the ground and load it into a van (Godoy, 2020). This tactic shows that the offender can steal motorcycle when opportunity presents itself.…”
Section: Introductionmentioning
confidence: 91%
“…National Insurance Crime Bureau (2020) showed that the top 10 states in the world for motorcycle thefts in 2018 were California, Florida, Texas, New York, South Carolina, North Carolina, Indiana, Missouri, Georgia and Colorado. Besides that, theft of motorcycles is most commonly reported in the Philippines (Godoy, 2020) and it is also contributing a major form of property crime in Nigeria (Ogundipe & Ojedokun, 2017). In Malaysia, government preventions of motorcycle theft are being carried out through better lighting hot spot parking areas, promotion of use of anti-theft U-locks, and using decoys (Hamidi, 2015).…”
Section: Introductionmentioning
confidence: 99%